PENGARUH PENGHARGAAN, STRES KERJA, DAN MOTIVASI KERJA TERHADAPA KINERJA KARYAWAN (PADA PT. ENSEVAL PUTERA MEGATRADING TBK CABANG MALANG) - Ahmad Haidir Arafat; Hadi Sunaryo; Muhammad Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT: The purpose of this study are 1) description of the award, work stress and work motivation on the performance of employees of PT. Enseval Putera Megatrading. 2) knowing and analyzing rewards has a significant influence on employee performance variables PT. Enseval Putera Megatrading. 3) knowing and analyzing work stress has a significant influence on employee performance variable PT. Enseval Putera Megatrading. 4) Know and analyze the motivation has a significant influence on employee performance variable PT. Enseval Putera Megatrading. 5) to know the variables of appreciation, work stress and work motivation simultaneously on employee performance in PT.Enseval Putera Megatrading. Samples used are employees of PT. Enseval Putera Megatrading Malang Tbk, Malang Branch as many as 60 respondents. Data collection methods used are questionnaire (questionnaire) and interview (interview).The result of the research shows that the awards have a significant effect on the performance of the employees of PT. Enseval Putera Megatrading Tbk Malang Branch, work stress does not significantly affect the performance of employees of PT. Enseval Putera Megatrading Tbk Malang Branch, work motivation significantly influence the performance of employees of PT. Enseval Putera Megatrading Tbk Malang Branch, awards, job stress and work motivation together effect on employee performance at PT. Enseval Putera Megatrading Tbk, Malang Branch.Keywords: rewards, job stress and employee performance